Magneto spectroscopy of single-walled carbon nanotubes - Portugall, Oliver; Krstic, Vojislav; Rikken, Geert L.J.A.; Kono, Junichiro; Shaver, J.; Zaric‬, ‪Sasa; Moore, Valerie C.; Hauge, Robert H.; Smalley, Richard E.; Miyauchi, Y.; Maruyama, Shigeo (International Journal of Modern Physics B, 2007)
Carbon nano-tubes (CNTs) are attracting tremendous interest as the object of fundamental studies in condensed matter and molecular physics as well as possible functional units for future nano-devices. Some of the most striking features of CNTs are related to the symmetry breaking effect of high magnetic fields threading the tube axis. In the present paper we review the results of recent magneto-optical studies of single-walled CNTs in pulsed magnetic fields up to 71 T and at temperatures between 4.2 and 300 K. We present clear evidence for (a) the effect of the Aharonov-Bohm phase on the bandstructure of CNTs, (b) the existence of dark excitons in CNTs due to Coulomb mixing and (c) the effect of magnetic brightening, i.e. the increase of the quantum yield of CNTs under the influence of an external field. Experimental data was derived from large ensembles of individualized tubes in either aligned films or in liquid suspension. A brief discussion of the effect of dynamic magnetic alignment of suspended tubes will be included.
Keywords: Carbon nanotubes; Dark excitons; Aharonov-Bohm effect; Photoluminescence; Pulsed magnetic fields